PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN MANAJEMEN PENDIDIKAN DI SMPN 4 BANJARMASIN - Sunarti Sunarti (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2020)
Schools as formal educational institutions that have separate management in the management of education, have thus become increasingly necessary. Therefore collaboration between public agencies should be developed in synergy, given the interests and ideals alike that saves and brighten the future of our nation. Forms of community participation in education in SMPN 4 Banjarmasin quite diverse, namely 1) participation as a board member school committee, 2) participation in various activities at the school, and 3) community participation in maintaining security madrasah. Strategies and approaches that have been done in order to foster and develop community participation in education in SMPN 4 Banjarmasin covers three areas: 1) Identify the Problem; 2) The treatment and approach; and 3) Guidance.Keywords: Management, and Public Participation.